Excess of Rare Missense Variants in Hearing Loss Genes in Sporadic Meniere Disease - Gallego-Martinez, Alvaro; Requena, Teresa; Roman-Naranjo, Pablo; Lopez-Escamez, Jose A. (Frontiers in Genetics, 2019)
Meniere’s disease (MD) is a clinical spectrum of rare disorders characterized by vertigo attacks, associated with sensorineural hearing loss (SNHL) and tinnitus involving low to medium frequencies. Although it shows familial aggregation with incomplete phenotypic forms and variable expressivity, most cases are considered sporadic. The aim of this study was to investigate the burden for rare variation in SNHL genes in patients with sporadic MD. We conducted a targeted-sequencing study including SNHL and familial MD genes in 890 MD patients to compare the frequency of rare variants in cases using three independent public datasets as controls. Patients with sporadic MD showed a significant enrichment of missense variants in SNHL genes that was not found in the controls. The list of genes includes GJB2, USH1G, SLC26A4, ESRRB and CLDN14. A rare synonymous variant with unknown significance was found in the MARVELD2 gene in several unrelated patients with MD. There is a burden of rare variation in certain SNHL genes in sporadic MD. Furthermore, the physical interaction of specific gene variants at protein level can explain the additive effect of rare variants in different genes in MD. This study will contribute to design a gene panel for the genetic diagnosis of MD.